The effects of cryptocurrencies, exchange rates, and gold prices on the share prices on infobank15 index in 2018-2021 with inflation as a moderation variable - Wahid Ruhiyat; M.Titan Terzaghi (Enrichment : Journal of Management, 2023)
This research aimed to determine and analyse the effect of cryptocurrency, exchange rates, and gold prices on Infobank15 Index Stock Prices for 2018-2022, with inflation as a moderating variable. This study employed a quantitative method, and an explanatory research design explained the effect of one variable on another. This study comprised up to 48 populations of Infobank15 Index data, cryptocurrencies, exchange rates, gold prices, and Inflation monthly from 2018 to 2021. Stock prices were affected by cryptocurrency, exchange rates, and gold prices simultaneously. The effect of cryptocurrency and exchange rates on stock prices can be moderated by inflation; however, it could not moderate the effect of gold prices on stock prices. Since the entire population served as the sample, the saturated sampling method was utilised in this research. The technique for analysing data employed multiple linear regression and moderation regression analysis using the SPSS software. The findings indicated that cryptocurrency had a positive effect on stock prices; on the other hand, exchange rates had a negative impact, and gold prices had no effect. Stock prices were affected by cryptocurrency, exchange rates, and gold prices simultaneously. The effect of cryptocurrency and exchange rates on stock prices can be moderated by inflation; however, it could not negotiate the effect of gold prices on stock prices.